Atributos funcionais de caatinga, uma floresta sazonalmente seca: estratégias, distribuição espacial, interações entre plantas e restauração de comunidades - Fagundes, Marina Vergara (2020)
Functional traits are all physiological, morphological anatomical and biochemical features of an organism that allow it to survive and reproduce in its environment. The functional traits of organisms, here limited to tree species, in a given region, are primary selected by environmental filters. The understanding of how the environment modulates vegetation community is a worldwide question in Ecology. Once limited by environmental conditions, the functional traits will also exert effects on its environment, by changing abiotic resources and condition, affecting the surrounding organisms. Such effect can also modulate community structures. Understand both processes its fundamental to the understanding not only general ecological patterns, but to generate information in order to apply ecological theories to rebuild communities as in restoration programs. Mentioned that, this work is made by 3 independent chapters all focused in Seasonal dry Forest Caatinga. The first chapter aim to analyzed tree species coordinated trade-offs of one of the most biodiverse Seasonal tropical dry forest, determined its functional groups gathering above-below ground and biochemical traits, test if these groups are spatially associated over the biome and if the distribution is limited to a aridity gradient. We sampled several anatomical, physiological, structural and biochemical functional traits of adult tree species in situ, and young plants of 2 and 6 months old cultivated in a greenhouse. We performed PCA test, K-means. Ripleys K analysys and gls to respond the aforesaid questions, respectively. We found distinct coordinated trade-offs representing the slow-fast growth strategies continuum. This continuum were collapsed in two main groups of acquisitive and conservative strategies, and the majority of species were selected to conservative group. Species of both groups are independently distributed over the biome, and fast-strategy species occurrence is more related to arid regions than slow-strategies. The second chapter aim to test which functional traits are important to explain facilitation capabilities of nurse plants, and if specific combinations of nurse-target functional traits explain the outcome of species-specific interaction. We performed a in-situ experiment with 60 adult plant-target tree species combination replicated 5 times. Using the already sampled functional traits as predictive variable and plant neighbour performance as response variable, we performed a GLMM followed by variable simplification. We found that both conservative and acquisitive species can exert positive effects and the outcome is highly dependent on the pair of species match. The positive outcome however, happened when the species exerting the effect, had functional traits which effect on environment, fulfill the ecological above- or below-ground requirements of its plants neighbour. At least, the third chapter, aim to disentangle the facilitation from functional complementarity effects, and test the importance of this components on biomass production and community function. We produced 4704 seedlings of 16 semiarid tree species using a new growing method. All individuals were planted in 147 experimental build communities of 13 m X 18 m, with 32 individuals each. The experimental communities were build at five levels of diversity and with distinct composition at each level replicated three times. The biomass production and the Net biodiversity Effect (NBE) were calculated and used as response variables. As a predictive variables we used facilitation community potential, community weighted mean and functional diversity based on above and below-ground traits. For both response variables, we performed a generalized linear mixed models to understand how they drive the productivity and function of communities. We showed that facilitation is a key process for restoration acting since the community biomass productivity until its net biodiversity effects. Both parts of complementarity effect, functional diversity and facilitation, are fundamental for a higher community function at the initial years of rebuilt communities.Additionally, we showed how to manipulate the three components of the Net biodiversity Effect, facilitation, functional diversity and community functional identity, in order to guide future restoration programs.